The complete chloroplast genome of Scutellaria indica var. coccinea (Lamiaceae), an endemic taxon in Korea - Yoonkyung Lee; Sangtae Kim (Mitochondrial DNA. Part B. Resources, 2019)
Scutellaria indica var. coccinea (Lamiaceae) is an endemic taxon in Jeju Island, Korea. We present the complete chloroplast genome sequence of S. indica var. coccinea. Its genome size is 151,956 bp in length comprising a large single copy of 83,951 bp, a small single copy of 17,539 bp, and a pair of inverted repeats measuring 25,233 bp. The complete genome contains 115 genes including 80 protein-coding genes, four rRNAs, and 31 tRNAs. Phylogenetic analysis of this species with 10 published chloroplast genomes in Lamiaceae showed that S. insignis is a sister to S. indica var. coccinea.